2017
DOI: 10.1111/pbr.12524
|View full text |Cite
|
Sign up to set email alerts
|

QTL for maize grain yield identified by QTL mapping in six environments and consensus loci for grain weight detected by meta‐analysis

Abstract: Grain yield is the most important and complicated trait in maize. In this study, a total of 498 recombinant inbred lines (RIL) derived from a biparental cross of two elite inbred lines, 178 and P53, were grown in six different environments. Quantitative trait locus (QTL) mapping was conducted for three grain yield component traits (100 grain weight, ear weight and kernel weight per plant). Subsequently, meta‐analysis was performed after a comprehensive review of the research on QTL mapping for grain weight (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Three of the regions where significant SNPs associated with grain yield under high pressure of corn borer were detected (~ 199–202 Mb in chromosome 1, ~ 128 Mb in chromosome 5, and ~ 6–12 Mb in chromosome 9) were close (~ 0.2 Mb) or within 3 meta-QTL for grain yield detected by Wang et al [78]. In chromosome 1, a meta-QTL containing a high number of individual QTLs and spanning between ~ 200 and ~ 208 Mb was also detected by Pan et al [79]. In addition, the analysis of Wang et al [78] identified a meta-QTL at ~ 197–198 Mb in chromosome 1, very close to the previously mentioned.…”
Section: Discussionmentioning
confidence: 56%
“…Three of the regions where significant SNPs associated with grain yield under high pressure of corn borer were detected (~ 199–202 Mb in chromosome 1, ~ 128 Mb in chromosome 5, and ~ 6–12 Mb in chromosome 9) were close (~ 0.2 Mb) or within 3 meta-QTL for grain yield detected by Wang et al [78]. In chromosome 1, a meta-QTL containing a high number of individual QTLs and spanning between ~ 200 and ~ 208 Mb was also detected by Pan et al [79]. In addition, the analysis of Wang et al [78] identified a meta-QTL at ~ 197–198 Mb in chromosome 1, very close to the previously mentioned.…”
Section: Discussionmentioning
confidence: 56%
“…When the phenotypes of different traits of a maize population were assessed, it was found that the low-P tolerance in different genotypes was significantly correlated with the phenotype of plants under low P. Both can be used for screening and genetic analysis of low-P tolerant germplasm [41] . According to the definition of PUE, biomass and yield are still the main selection criteria when screening for P-efficient germplasm, but both traits are very complex quantitative traits controlled by many minor QTL [42][43][44] .…”
Section: Genotypic Differences In Response To Low-p Starvation In Maizementioning
confidence: 99%
“…Several researchers have reported that yield contributing traits usually exhibit stable QTLs across environments (MESSMER et al, 2009;LIU et al, 2014;ZHANG et al, 2017). Till today various researchers carried out QTL analysis for various yield traits, namely those related to ear morphology (EL, ED) (MENDES-MOREIRA et al, 2015;CHEN et al, 2016;SU et al, 2017), KR/E (VELDBOOM and LEE, 1994;AUSTIN and LEE, 1996), K/R (CHEN et al, 2016;SU et al, 2017), TW (CHEN et al, 2016;PAN et al, 2017;SU et al, 2017;ZHAO et al, 2018) and GY/P (VEIGA et al, 2012;CHEN et al, 2016;SU et al, 2017;NIKOLIC et al, 2018;RIBEIRO et al, 2018). To date, many QTLs for yield contributing traits were discovered of which 45 QTLs were associated with ED, 149 with TW, 46 with EL, and 23 with KR/E (https://archive.gramene.org/qtl/).…”
Section: Introductionmentioning
confidence: 99%